Conceptual Knowledge, Experiences, and Sources of Information Secondary School Students Have About Owls - Said Doğru, M. (International Council of Associations for Science Education, 2022)
This study examined the level of knowledge the students had about owls by means of drawings and written answers. In the interviews, the students in the lower grades were found to have more limited information and less biological literacy than the ones in the upper grades. The aim was to determine students’ knowledge, experience, and sources of information about owls, and then to determine how useful they were by comparing information obtained from drawings and written answers to previous research conducted with students. A total of 878 students in the sixth and seventh grades in Turkey participated in the research. The students were familiar with certain characteristics of owls. The drawings provided clearer information about body parts and proportions, while the specific habitats, behaviors, and feeding of owls were expressed in more detail in the written responses. The students without any experience with owls were inadequate in reporting information about owls. When the frequencies of responses in the general concept categories about owls were compared, it was found that the use of drawings and written answers was equally beneficial for upper and lower grade students. It would be better to determine the views and sources of information of secondary school students through drawings and written answers to assess whether they have understood the concepts related to science subjects.
Keywords: Science; Q; drawings and written answers of students; Theory and practice of education; secondary school students; conceptual information about owls; LB5-3640; their experiences; 4. Education